Pengembangan Permakultur di Sekolah Alam Bengawan Solo di Desa Gondangsari, Juwiring Klaten - Rahmasari, Lita (Prosiding KPSDA, 2015)
This community services was intended to optimize the activity of CLC Youth Model, increasing the natural potential for learning activities, exploiting the potential of the watershed to improve the economy of the community The method presented in optimizing the management of CLC, the concept Permaculture. Concept Permaculture (permanent agriculture and permanent culture) in which there are elements of education, community development, and entrepreneurship has great potential to be applied in the village Gondangsari by integrating the activities of CLC. The concept of permaculture that will implementate in Gondangsari Village, Juwiring, Klaten form of priority programs, such as programs in the areas of education, skills, entrepreneurship, agriculture and livestock, as well as the processing of agricultural products. Meanwhile, the activities that can be done is to use less productive land into an area that can benefit peoples lives through the concept of permaculture.